1994
DOI: 10.1111/j.1365-2362.1994.tb02253.x
|View full text |Cite
|
Sign up to set email alerts
|

α‐Glucosidase inhibitors in diabetes: efficacy in NIDDM subjects

Abstract: With α‐glucosidase inhibitors generally improved metabolic control is achieved in NIDDM patients regardless of whether acarbose is administered in addition to other oral anti‐diabetic agents or to diet alone. The most significant finding is the reduction of postprandial blood glucose concentrations. Long‐term studies show a decrease in glycosylated haemoglobin and often also in fasting blood glucose levels. Placebo‐controlled studies have proven that postprandial insulin concentrations are decreased under acar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
5

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(71 citation statements)
references
References 37 publications
0
66
0
5
Order By: Relevance
“…Alpha-glucosidase inhibitors inhibit the disaccharide digestion and impede the postprandial glucose excursion to enable overall smooth glucose profile (Casirola and Ferraris, 2006). Several alpha-glucosidase inhibitors have been isolated from medicinal plants to develop as an alternative drug with increased potency and lesser adverse effects than the existing drugs (Toeller, 1994). Our in vitro studies, had shown that the polysaccharide samples isolated form the eight studied Aloe species had some inhibitory activities on the alpha-glucosidase enzyme (Table 3).…”
Section: Discussionmentioning
confidence: 92%
“…Alpha-glucosidase inhibitors inhibit the disaccharide digestion and impede the postprandial glucose excursion to enable overall smooth glucose profile (Casirola and Ferraris, 2006). Several alpha-glucosidase inhibitors have been isolated from medicinal plants to develop as an alternative drug with increased potency and lesser adverse effects than the existing drugs (Toeller, 1994). Our in vitro studies, had shown that the polysaccharide samples isolated form the eight studied Aloe species had some inhibitory activities on the alpha-glucosidase enzyme (Table 3).…”
Section: Discussionmentioning
confidence: 92%
“…They may act as inhibitors of amylase and glucosidase (similar to acarbose, miglitol and voglibose) leading to a reduction in post-prandial hyperglycemia (Bailey 2001). Synergy between phenolics and dietary fiber may play a role in mediating amylase inhibition and therefore, have the potential to contribute to the management of type II Diabetes mellitus (Saito et al 1998;Toeller 1994). Chethan et al (2008a) studied the mode of inhibition of finger millet malt amylases by the millet phenolics and reported that the crude polyphenolic extract exerts mixed non-competitive type inhibition, whereas the individual phenolic compounds isolated from the extract exhibit uncompetitive inhibition.…”
Section: Inhibition Of Malt Amylases Pancreatic Amylase Intestinal mentioning
confidence: 99%
“…Among the many therapies, decreasing postprandial hyperglycemia is considered to be the best therapeutic approach (Park et al, 2013;Toeller, 1994). It is achieved through retarding the absorption of glucose by inhibiting activities of the carbohydrate hydrolyzing enzymes (a-amylase and a-glucosidase) in the digestive tract.…”
Section: Introductionmentioning
confidence: 99%